Liposclerosing myxofibrous tumor of the distal femur: A case report - Zhang, Mingyang; Zhang, Daguang; Yu, Wenjiang; Wang, Chengxue (Frontiers in Surgery, 2023)
Introduction: Liposclerosing myxofibrous tumor (LSMFT) is a rare benign fibro-osseous tumor that most frequently occurs in the proximal femur. The reported literature shows that the proximal femur, ilium, tibia, humerus, rib, and skull have occurred, but so far, the female distal femur has not been characterized in detail. This, we think, is the first single comprehensive case report of the female distal femur. To prevent misdiagnosis and overtreatment of this illness, it is critical for us to continue strengthening our knowledge of it and to add it to the differential diagnosis of the space-occupying lesion of the female distal femur. Case Summary: Two months ago, a 55-year-old female patient was found to have a space-occupying lesion of the left distal femur and the pain symptom was aggravated. She underwent thorough curettage and bone grafting without additional treatment to relieve the current symptoms and determine the nature of the lesion in our hospital. The intraoperative specimens were submitted to the pathology laboratory for analysis, and the result was reported to LSMFT. And six months after the operation, the patient returned to our hospital for another X-ray examination and we found that she had recovered well without any signs of recurrence. The patient self-reported that she had now resumed her daily life without any uncomfortable symptoms. Conclusion: The incidence of LSMFT itself is relatively low, and the occurrence of the distal femur is even rarer. However, it is recommended to add LSMFT into the differential diagnosis of the occupying lesions of the distal femur. Once the diagnosis is made, thorough curettage and bone grafting without additional special treatment can achieve better postoperative outcomes.